SENTIMENTAL ANALYSIS OF SPORTS CONSUMER BEHAVIOUR AND ASSOCIATED BRANDING ACTIVITES USING PARTICLE SWARM OPTIMZATION (PSO) - PM, Umarani; Dhanya, D. (International Journal of Psychosocial Rehabilitation, 2020)
Nothing brings together the passions and emotions of people like sports do. Companies are increasingly apportioning a major part of their annual advertising budgets on sports. Sponsoring tournaments, teams, or sports stars, companies in essence buy the rights to use those properties for their benefit. As title sponsor of the T20, mobile wallet company PayTM spent Rs 5-6 crores for two matches. In return, a huge blue coloured logo appeared across the stadium and on field. In 2015, home grown mobile behemoth Micromax was outsmarted by this start-up PayTM for Board of Control for Cricket(BCCI) four-year title sponsorship. It was for domestic and international cricket matches at home. This work highlights sentimental analysis using PSO to trade off the sponsorship analysis between the product and the sport along with the heights of overall benefits that reflects in game and the brand.